2021
DOI: 10.1021/acs.jpclett.1c01253
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Type and Pathways Are Governed by the Forces of Protein–Ligand Binding

Abstract: Allostery is central to many cellular processes, by up-or down-regulating target function. However, what determines the allosteric type remains elusive and currently it is impossible to predict whether the allosteric compounds would activate or inhibit target function before experimental studies. We demonstrated that the allosteric type and allosteric pathways are governed by the forces imposed by ligand binding to target protein using the anisotropic network model and developed an allosteric type prediction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 64 publications
(83 reference statements)
1
24
0
Order By: Relevance
“…Another latest success in computationally characterizing the modulatory impacts of allosteric ligands is the tool AlloType, 247 which deploys a thermodynamic model to predict the modulatory mechanisms of allosteric modulators. Energetic changes during substrate binding are quantified as readouts of the influence conferred by allosteric binding.…”
Section: Characterization Of Allosteric Modulatorsmentioning
confidence: 99%
“…Another latest success in computationally characterizing the modulatory impacts of allosteric ligands is the tool AlloType, 247 which deploys a thermodynamic model to predict the modulatory mechanisms of allosteric modulators. Energetic changes during substrate binding are quantified as readouts of the influence conferred by allosteric binding.…”
Section: Characterization Of Allosteric Modulatorsmentioning
confidence: 99%
“…Many studies have shown that the level of GPX4 increases following the administration of puerarin. Moreover, Huang et al [ 63 ] reported that compound 1d4 can be an allosteric activator to activate GPX4 for connecting with the key allosteric site (D21 and D23) and key catalytic residues (C46, Q81, K90, W136 and so on). Meanwhile, the result of molecular docking predicted that puerarin may bind to GPX4 with residues ASP21, ASP23, LYS90 and ASP101.…”
Section: Discussionmentioning
confidence: 99%
“…23,28,29 It can also be combined with the linear response theory to describe the conformational changes upon ligand binding and the resulting allostery. 26,30 The original ANM 29 regards the Cα atom of each residue in a protein as a node, and the node pairs within a cutoff distance are connected by harmonic springs with the same force constant, where the influence of side chains is not considered. Recently, Kaynak et al proposed a multiscale elastic network model, RESPEC, which includes side-chain information and protein−ligand interactions into the original ANM.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Here, we consider only the allosteric effect caused by the binding affinity and not the catalytic constant change, which requires quantum chemistry treatment. 30 A positive allostery (activation) occurs when ΔΔG < 0, while a negative allostery (inhibition) occurs when ΔΔG > 0. For the dynamic allostery, the structures do not change after ligand binding and the enthalpic contribution to ΔΔG becomes zero.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%